The Effect of Self-Efficacy on Students’ Mathematical Abilities: A Meta- Analysis Study - Kamsurya, Marwa Astriani; Wijaya, Ariyadi; Ramadhani, Rahmi; Hukom, Julham (FKIP Universitas Lampung, 2022)
Objective: This study investigates the effect of diei efficacy on students' mathematical abilities. Methods: The research design used in this study is a meta-analysis by analyzing 16 studies published in journals indexed by SCOPUS with a sample of 73935 people in various countries. To support the accuracy of the analysis results, OpenMEE software is used. Findings: The results revealed that the combined effect size values generated using the random-effect model estimate were (g = 0.518; p < 0.001) with a standard error (SE = 0.031). This effect size belongs to the medium effect category. Conclusion: Thus, it can be concluded that self-efficacy has a positive and significant effect on students' mathematical abilities.Keywords: mathematics ability, self-efficacy, and meta-analysis.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202205